2017
DOI: 10.1002/lno.10763
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of dietary phosphorus and iron on Daphnia life history

Abstract: Food quality of freshwater consumers is often defined as the relative supply of carbon (C) to phosphorus (P) in diet. The growth rate hypothesis makes mechanistic links between P supply, ribosome biogenesis, and growth, with subsequent impacts on other life history traits such as age at maturity and clutch size. However, we know surprisingly little about the role and importance of other elements in impacting life histories of freshwater zooplankton. Because there is much evidence indicating a pivotal role for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 56 publications
(76 reference statements)
4
15
0
Order By: Relevance
“…Algal stoichiometry is an important factor regulating zooplankton growth rates, reproductive traits, and population growth (Lind & Jeyasingh, 2017). Moreover, we do not understand how changes in species composition will affect higher trophic levels.…”
Section: Basal Trophic Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Algal stoichiometry is an important factor regulating zooplankton growth rates, reproductive traits, and population growth (Lind & Jeyasingh, 2017). Moreover, we do not understand how changes in species composition will affect higher trophic levels.…”
Section: Basal Trophic Levelsmentioning
confidence: 99%
“…For example, changes in the occurrence of various diatoms or phytoplankton species may correspond to stoichiometric changes of algal food resources. Algal stoichiometry is an important factor regulating zooplankton growth rates, reproductive traits, and population growth (Lind & Jeyasingh, 2017). Thus, future research on patterns of change in phytoplankton and photosynthetic periphyton species and the implications of such change is needed.…”
Section: Diatoma Vulgaris Encyonema Caespitosum Pinnularia Microstamentioning
confidence: 99%
“…). Ionome‐wide information is also important when studying the consequences of evolution on the flow of nutrients between organisms and their environment, as the availability, uptake, and utilization of specific macronutrients is often dependent on the dynamics of trace elements (Lind & Jeyasingh ; Liu et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased elemental resolution provides an enhanced ability to identify the axes of ecologically relevant variation among populations, which could be useful in identifying the phenotypic underpinnings of local adaptation (Huang & Salt 2016;Goos et al 2017). Ionome-wide information is also important when studying the consequences of evolution on the flow of nutrients between organisms and their environment, as the availability, uptake, and utilization of specific macronutrients is often dependent on the dynamics of trace elements (Lind & Jeyasingh 2018;Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3b), a gene family essential for iron metabolism in many organisms 40 . Previous research in Daphnia identified a significant interaction between P-limitation and iron-kinetics 41 . This finding, together with our results suggests a central role of MCOs in modulating essential cellular processes under P-limitation.…”
Section: Resultsmentioning
confidence: 91%